UPAH MINIMUM PROVINSI (UMP) DAN UPAH MINIMUN KABUPATEN / KOTA (UMK) DI PROVINSI BALI - Supartha, Wayan Gede (PIRAMIDA, 2012)
Minimum wages province and regency is public policy created by Governor in each provinces. The objective of minimum wages rate is to increased labour welfare and stable economic growth. The councils wages provinces has authority to decided wages minimum rate in each provinces and Governor declared minimum wages rate. The member of councils wages provinces, i.e, member of labour unions, member of enterprenuer unions, and government staff and university lecture. The councils wages provinces dicided minimum wages provinces and regency rate, annually base on ; expenditure need satisfaction, economic growth, labour productivity, ability to pay of marginal company, unemployment and minimum wages rate, of near other regencies. But the dominant factor to fixed minimum wages rate are expenditure need satisfaction and ability to pay of marginal company. To evaluate the labour welfare, we can take ratio beetwen minimum wages provinces and regency rate, to expenditure need satisfaction. If this ratio near or equal to one hundred procent, it is meant the labour welfare is enough. The fact in Bali Provinces shows that the ratio of minimum wages rate to expenditure need satisfaction are not reach one hundred procent. But its ratio was increased from 2006 to 2007. That?s meant labour welfare is increased in Bali Provinces.
Keywords: Minimum wages provinces and regency rate, expenditure need Satisfaction, economic growth, labour productivity, ability to pay of marginal company, unemployment and minimum wages rate, of near other regency.